Pengolahan data menggunakan Toolspack Analysis Excel pada guru-guru di Kabupaten Takalar - Rusli Rusli; Abdul Rahman; Ansari Saleh Ahmar; Sahid Sahid; Hastuty Hastuty (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Data processing using the Anaysis Toolspack is carried out in the form of training for junior high school teachers in Takalar district, in collaboration with the education and culture department of youth and sports in Takalar district. The training was attended by 34 teachers who were held in the office of the education and culture culture of the youth and sports district of Takalar. The purpose of this training is for skilled teachers to use statistical packages owned by Excel to process data and process data into one information. The results of the training show that the average ability of teachers to use statistics in the excel analysis toolspack package in processing and processing data after training is better than before training